Gastrocnemius Tendon Rupture in a Bitch - Ultrasonographic Diagnosis - Anna Vitória Hörbe; Catherine Konrad Nava Calva; Raquel Baumhardt; Fabiano da Silva Flores; Ingrid Rios Lima Machado; Felipe Auatt Batista de Sousa; Ricardo Pozzobon (Acta Scientiae Veterinariae, 2024)
Background: The gastrocnemius tendon, a crucial component of the common calcaneal tendon (CCT), plays an integral role in tarsal extension and knee flexion, thereby ensuring joint stability and supporting body weight during locomotion. Diagnosis is based on a comprehensive clinical and orthopedic examination supplemented by complementary imaging tests. CCT ruptures are uncommon, and ultrasound findings unique to the gastrocnemius component have been scarcely documented. This report aims to describe the ultrasonographic findings of a gastrocnemius tendon rupture in a dog - a topic not extensively covered in the literature, emphasizing the importance of ultrasound in diagnosing such ruptures. Case: A 4-year-old bitch greyhound weighing 20 kg was brought to a University Veterinary Hospital for a clinical evaluation due to acute lameness in the left hind limb. During the orthopedic examination, the patient presented with grade III lameness, bearing weight, supporting the limb with pincers, and exhibiting discomfort on palpation of the caudal region of the left hindlimb near the calcaneal tuberosity. This presentation prompted a suspicion of CCT rupture, leading to an ultrasound examination. For the ultrasound evaluation, after cleaning the trichotomized area, the conductive gel was applied, and the linear transducer was positioned at a frequency of 8-10 MHz, making direct contact and remaining perpendicular to the evaluated area. To achieve a comprehensive scan, images were captured along the entire length, from the proximal region at the myotendinous junction to the distal region at the site of insertion of the CCT into the calcaneal tuberosity. The assessment of the contralateral (lame) limb was subsequently carried out using the same method. The images obtained from the right pelvic limb indicated normal tendon structures, with preserved echotexture and morphology. Conversely, the left hind limb displayed intact common and superficial digital flexor tendons, a heterogeneous and substantially hypoechoic appearance of the gastrocnemius tendon, and an adjacent hematoma. These findings were consistent with a partial CCT rupture involving the gastrocnemius component. During the surgical procedure, the rupture of the gastrocnemius tendon, as well as the integrity of both the superficial digital flexor tendon and the common tendon, were confirmed. The procedure involved tenorrhaphy of the gastrocnemius tendon and the temporary arthrodesis of the tarsus using a transarticular pin. Tibiotarsal immobilization was maintained for three weeks post-surgery. Upon immobilization removal, the patient demonstrated good recovery and functional return of the limb. Discussion: Partial ruptures of CCT only involving the gastrocnemius component have been poorly described in the veterinary literature. While radiography is the preferred method of examination to diagnose suspected orthopedic conditions, ultrasound is widely available in small animal care and highly accurate in detecting such tendon injuries, in addition to, in most cases, not requiring anesthesia. This report elucidates the ultrasonographic characteristics of a complete gastrocnemius tendon rupture, underscoring the important role of ultrasound in the diagnosis as it effectively differentiates between complete and partial tendon ruptures and acute and chronic tendinopathies. More importantly, its sensitivity in determining the lesion location and extent proves invaluable when clinical and orthopedic examinations are inconclusive. Hence, its utility as an auxiliary tool for evaluating tendon injuries is emphasized. Keywords: Achilles tendon, gastrocnemius, tendon injury, ultrasound. Título: Ruptura do tendão gastrocnêmio em uma cadela - diagnóstico ultrassonográfico Descritores: tendão de Aquiles, gastrocnêmio, lesão de tendão, ultrassonografia.